2019
DOI: 10.3390/w11102047
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Constraining Depositional Zones in a Tide-Influenced River: Insights from the Gorai River, Southwest Bangladesh

Abstract: The tidal to fluvial transition (TFT) of estuaries and coastal rivers is one of the most complex environments on Earth with respect to the transportation and deposition of sediment, owing in large part to competing fluvial and marine processes. While there have been recent advances in the stratigraphic understanding of the TFT, it is still unclear whether these findings are site-specific or representative of mixed tidal-fluvial systems worldwide. Yet, research from this depositional domain holds profound socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 90 publications
3
18
0
Order By: Relevance
“…Away from the main channels, though, active sediment deposition in the upper delta is still supported by secondary mechanisms. Large distributaries, such as the Madhumati‐Gorai and Arial Khan, divert ∼10 ± 5% of discharge from the main channels to remote delta‐plain areas, serving to offset slow subsidence (Bomer et al., 2019). Additionally, effective sediment redistribution in the distal floodplain is driven by local runoff and overland flow due to intense seasonal precipitation (Goodbred & Kuehl, 1998).…”
Section: Delta Network Connections and Landscape Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Away from the main channels, though, active sediment deposition in the upper delta is still supported by secondary mechanisms. Large distributaries, such as the Madhumati‐Gorai and Arial Khan, divert ∼10 ± 5% of discharge from the main channels to remote delta‐plain areas, serving to offset slow subsidence (Bomer et al., 2019). Additionally, effective sediment redistribution in the distal floodplain is driven by local runoff and overland flow due to intense seasonal precipitation (Goodbred & Kuehl, 1998).…”
Section: Delta Network Connections and Landscape Dynamicsmentioning
confidence: 99%
“…For distal areas of the lower delta plain, land surface elevations are sustained by secondary transport processes, as they are in abandoned areas of the upper delta. Indeed, the same distributaries from the upper delta do contribute some sediment and freshwater to the lower delta as well (Bomer et al., 2019); however, on the lower delta plain tides are the principal mechanism of sediment transport. There, flood‐dominant tidal transport extends 100 km inland of the coast and efficiently imports sediment from the river plume and resuspended sediment from the inner shelf (Bomer et al., 2020; Hale et al., 2019; Rogers et al., 2013).…”
Section: Delta Network Connections and Landscape Dynamicsmentioning
confidence: 99%
“…The tidal‐dominated landscape of the GBM Delta experiences semi‐diurnal mesoscale (2–4 m) tides. In the 1960s, the Bangladesh government began constructing earthen embankments to protect agricultural land from salinity incursion, and the land within the embankments is referred to as polders (Allison & Kepple, 2001; Ayers et al, 2017; Bomer et al, 2019; Bricheno et al, 2016). While the embankments provide a layer of protection, elevation surveys of Polder 32 from Auerbach et al (2015) revealed embanked elevations were 1.0–1.5 m below adjacent unembanked elevations in the Sundarbans, the world's largest mangrove preserve (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…About 41 percent of the cyclones originating in the Bay of Bengal travel through this funnel-shaped central region each year, such as Cyclone Sidr in 2007 (Ikeuchi et al, 2017), which makes the central coast of Bangladesh vulnerable to storm surge (Paul and Rahman, 2006). A complete analysis of processes that shape the landscape in this tidal-to-fluvial transition zone of Bangladesh is beyond the scope of this research but is detailed effectively elsewhere (Goodbred and Kuehl, 1999;Wilson and Goodbred, 2015;Bomer et al, 2019).…”
Section: Study Areamentioning
confidence: 99%